RHETORICAL STYLE IN LONGING EXPRESSION FOUND IN WILLIAM SAROYAN’S GOING HOME (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2012)
This study is about rhetorical style as a means of longing expression in William Saroyan’s short story. The problems of this study are what kinds of rhetoric which are used to express longing and why the author uses rhetorical style in his work. The objectives of this study are to find, describe, and explain the rhetorical style used in Saroyan’s story. Rhetorical features that are found in Saroyan’s story entitled Going Home are asyndeton, hyperbole, commoratio, anaphora, parison, polysyndeton, climax, simile, personification, and antithesis. In conducting the research, I read the short story and then identified the rhetorical features which are found in every word, phrase, and sentence in the text. I listed them in a table and then classified the collected data into their classification. In analyzing the data, I explain the definition of rhetorical features. Next I interpreted the data using my own words. The result of this study shows that there are 17 expressions that contain rhetorical features. By using rhetorical style, Saroyan wants to convey and emphasize about his concept of longing and also to give ornament in his short story.